2023
DOI: 10.4155/fmc-2022-0243
|View full text |Cite
|
Sign up to set email alerts
|

Propargylamine: an Important Moiety in Drug Discovery

Abstract: Propargylamine is a chemical moiety whose properties have made it a widely distributed group within the fields of medicinal chemistry and chemical biology. Its particular reactivity has traditionally popularized the preparation of propargylamine derivatives using a large variety of synthetic strategies, which have facilitated the access to these compounds for the study of their biomedical potential. This review comprehensively covers and analyzes the applications that propargylamine-based derivatives have achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…[16,17] Particularly, many groups have successfully developed hybrid molecules which, by incorporating a propargylamine function, show multitarget activity for neurodegenerative disorders, beyond MAO inhibition. [18][19][20] We have also recently applied this ligand-based design concept to develop propargylamine-featuring riluzole-rasagiline hybrids for amyotrophic lateral sclerosis (ALS). [21] Building on these results, we sought to combine the substituted bicyclic core of 1 and the neuroprotective propargylamine group into a single molecule (Figure 1).…”
Section: Design and Synthesis Of Hybridsmentioning
confidence: 99%
“…[16,17] Particularly, many groups have successfully developed hybrid molecules which, by incorporating a propargylamine function, show multitarget activity for neurodegenerative disorders, beyond MAO inhibition. [18][19][20] We have also recently applied this ligand-based design concept to develop propargylamine-featuring riluzole-rasagiline hybrids for amyotrophic lateral sclerosis (ALS). [21] Building on these results, we sought to combine the substituted bicyclic core of 1 and the neuroprotective propargylamine group into a single molecule (Figure 1).…”
Section: Design and Synthesis Of Hybridsmentioning
confidence: 99%
“…[25][26][27][28] Propargylic amines are important compounds in different fields especially in therapeutic drug molecules. [29][30][31] Nowadays, a typical method for preparation of propargylic amines includes one-pot catalytic reaction of aldehydes, alkynes, and amines, [32][33][34][35][36][37] which is more efficient and easier than traditional methods including reaction of imine with Grignard or lithium acetylides. 38,39 In 2003, Wei et al 40 reported gold catalyzed three-component reaction of alkyne, aldehyde, and amine in water.…”
Section: Introductionmentioning
confidence: 99%
“…Propargylamines are extensively used as versatile building blocks for the synthesis of functional organic molecules, drugs and natural products. 1 The cross-coupling of tertiary amines with terminal alkynes under oxidative conditions is one of the most powerful tools for the construction of these scaffolds. 2 Earth-abundant metal based catalysis is a prominent strategy for this transformation.…”
Section: Introductionmentioning
confidence: 99%